2008
DOI: 10.1161/strokeaha.108.521617
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm Growth Occurs at Region of Low Wall Shear Stress

Abstract: Background and Purpose-Evolution of intracranial aneurysmal disease is known to be related to hemodynamic forces acting on the vessel wall. Low wall shear stress (WSS) has been reported to have a negative effect on endothelial cells normal physiology and may be an important contributor to local remodeling of the arterial wall and to aneurysm growth and rupture. Methods-Seven patient-specific models of intracranial aneurysms were constructed using MR angiography data acquired at two different time points (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
220
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(235 citation statements)
references
References 29 publications
14
220
1
Order By: Relevance
“…In the past, research analyzing unruptured aneurysms found that aneurysm growth was likely to occur at low WSS areas. 23 Our data showed that changes in aneurysm shape are not restricted to low WSS regions. As previously reported by Kono et al 24 in a study of a single posterior communicating artery aneurysm, we also found WSS changes before and after rupture.…”
Section: Discussionmentioning
confidence: 47%
“…In the past, research analyzing unruptured aneurysms found that aneurysm growth was likely to occur at low WSS areas. 23 Our data showed that changes in aneurysm shape are not restricted to low WSS regions. As previously reported by Kono et al 24 in a study of a single posterior communicating artery aneurysm, we also found WSS changes before and after rupture.…”
Section: Discussionmentioning
confidence: 47%
“…Multiple applications of CFD for the evaluation of human flow characteristics have been reported in the past years including, for example, the simulation of time-resolved 3D flow patterns in the left ventricle, in geometrically complex aneurysms, or the carotid artery bifurcation (41)(42)(43)(44)(45). Such numerical simulations permit the detailed analysis of local flow patterns and calculation of additional relevant parameters such as pressure differences or wall shear rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, one can foresee several applications in the future: 1) predicting thrombosis in stented aneurysms, 6 and 2) adapting CFD to perioperative patient-specific conditions. Furthermore, an extension of the OF method in 3D would help give more quantitative insight on both the measurements of flow-pattern complexity and related parameters such as wall shear stress in aneurysms, which are believed to play an important role in all aspects of aneurysm growth, 9 rupture, 10 and clotting. compared the intra-aneurysmal flow structures of 3 patients between conventional DSA and virtual angiograms and were able to predict, with good agreement, the locations and sizes of the inflow jet, outflow, impaction zone, and vortex structures.…”
Section: Discussionmentioning
confidence: 99%